Towards and away from the body: The relevance of the direction of use in the coding of object-related actions. - Scotto di Tella, Gianluca; Ruotolo, Francesco; Ruggiero, Gennaro; Iachini, Tina; Bartolo, Angela (Quarterly Journal of Experimental Psychology, 2021)
This study examines whether the perception of an object automatically activates the representation of the direction of use of that object. To this aim, we carried out two experiments. In Experiment 1, participants were asked to explicitly categorise objects as used either away from the body (AB, for example, a hammer) or towards the body (TB, for example, a toothbrush). In Experiment 2, participants were asked to judge whether the same objects were natural or manmade. In both experiments, they were asked to respond by moving a joystick backwards (i.e., TB) or frontwards (i.e., AB). Therefore, their response could either be congruent (i.e., backward response with TB objects, frontward response with AB objects) or incongruent (i.e., backward response with AB objects, frontward response with TB objects) with the direction of object use. Results from Experiment 1 showed that in the congruent condition, participants were faster in judging the direction of object use than those in the incongruent condition (congruency effect). Crucially, results from Experiment 2 showed the presence of a congruency effect even when the direction of object use was task-irrelevant. However, this effect was found only for TB objects. These results suggest that the perception of TB objects automatically activates the direction of object use with respect to the body, thus showing evidence of direct connection between perception and action. A specific role of the body might account for different action representation processes involved in TB and AB object-related actions.